Numerical simulation of hydrate slurry flow and deposit behavior based on openfoam-IATE. (15th February 2022) - Liu, Xiang; Yuan, An; Li, Yuxing; Wang, Zhihua; Wang, Zhiyuan; Liu, Zhiming; Wang, Wuchang
Highlights: A dynamic model of hydrate agglomeration, breakage, nucleation and deposits insulation was proposed. The interface area transportation equation and convection heat transfer equation was implanted into OpenFOAM-4.x. The influences of flow rate, safe area for hydrate slurry flow and flushing were analyzed emphatically. The hydrate deposition morphology function was constructed by the principal component analysis method. Abstract: With the extension of oil exploitation from offshore to the deep sea, the development and utilization of natural gas hydrate have become one of the hottest energy issues. However, the agglomeration between hydrate particles will lead to severe pipeline hydrate plugging. Therefore, a dynamic model considering phase change about hydrate formation and decomposition as well as aggregation was proposed based on the interface area transportation equation and convection heat transfer equation, and then used to simulate hydrate slurry flow in this study. By integrating with traditional solid-liquid flow models, the aggregation, breakage, nucleation of hydrate particles, and deposits insulation were all considered in CFD software OpenFOAM-4.x. The influences of flow rate and the safe area for hydrate slurry flow were analyzed emphatically. Results show that flushing has a good dissociation effect on hydrate deposits formed by low-concentration slurry. By comparing deposition conditions of different concentrations and flow rates, it can be seen that high-concentration slurry results in a larger slope and thickness of the deposition front, while the flow rate mainly affects the extension of the deposits length. With the increase of the flow rates, the hydrate deposits evolve from belt-like deposits to point-like deposits. In addition, the hydrate deposition morphology function of different working conditions was constructed by the principal component analysis method.